O caso da utilização de créditos de PIS/Cofins na aquisição de insumos recicláveis: um estudo a partir do princípio da não cumulatividade e da extrafiscalidade - Marina Machado Marques (2023)
The article 47 of Law No. 11,196/05 prohibited the use of PIS/Cofins credits in the acquisition of recyclable inputs, while article 48 of the same law prescribed the suspension of contributions in the sale of these inputs to legal entities that calculate the corporate income tax based on taxable income. Recently, the Federal Supreme Court tried RE No. 607.109/PR, declaring both provisions unconstitutional, considering that the declaration of unconstitutionality only of article 47 of Law No. 11.196/05 would go against the logic of the non-cumulativity of PIS/ Cofins. In this scenario, the present research has the general objective to investigate, in the light of the principle of non-cumulativity and of the non-fiscal purpose of tax law, whether the right to the use of the credit on such acquisitions depends on the removal of the suspension provided for operations. For this purpose, a theoretical research on tax cumulativity, the principle of non-cumulativity and the impacts of exemptions granted at intermediate stages of a productive chain were carried out. Furthermore, the recycling sector, taxation and extrafiscality in relation to the recycled product were studied. In the end, it was observed that the declaration of the unconstitutionality of article 48 of Law No. 11,196/05 was not necessary in view of the non-cumulativity, given that the taxation of recycled materials results to the payment of taxes on the same material more than once, which generates cumulativity. Furthermore, depending on the agents involved and the respective tax regimes, the prohibition of the credit of contributions results in the impossibility of crediting the tax collected in the stages prior to the suspension. Moreover, the infra-constitutional legislation admits the right to credit in relation to exempt acquisitions. Finally, the maintenance of the suspension and the simultaneous right to the credit are also justified on extrafiscality reasons grounds, given the importance of recycling for environmental protection.